"No‐one's driving this bus" – qualitative analysis of PrEP health promotion for Aboriginal and Torres Strait Islander gay and bisexual men. (5th December 2018) - Hope, Alec; Haire, Bridget
Abstract: Objective : HIV prevention tools such as pre‐exposure prophylaxis require equitable access and uptake to protect all at‐risk populations. This project assessed the perceived barriers to accessible HIV prevention for Aboriginal and Torres Strait Islander gay and bisexual men (GBM) and evaluated the presence of health promotion for pre‐exposure prophylaxis (PrEP) for this population from the perspective of service providers. Methods : Eighteen semi‐structured interviews with healthcare providers, researchers and AIDS Council employees were qualitatively analysed for themes and concepts related to PrEP‐specific health promotion. Results : Respondents noted AIDS Councils and affiliated sexual health clinics had been instrumental in promoting PrEP to at‐risk GBM. However, many Aboriginal gay and bisexual men who are not well connected with these communities and services may not have been exposed to this health promotion and therefore have not accessed PrEP effectively. Conclusions : Aboriginal community and gay community controlled health organisations need to collaborate to ensure they deliver effective and tailored health promotion to Aboriginal communities. Implications for public health : The rising HIV notification rates in Aboriginal Australians is an example of the health gap experienced by First Nation people. Effective HIV prevention is required to ensure this gap does not widen further, and that Australia meets its goal of preventing all new HIV infections. However, these efforts will be hampered by ineffective health promotion of HIV prevention tools, such as PrEP, for Aboriginal Australians.